ENIGMA and global neuroscience: A decade of large-scale studies of the brain in health and disease across more than 40 countries - Thompson, Paul M; Jahanshad, Neda; Ching, Christopher R K; Salminen, Lauren E; Thomopoulos, Sophia I; Bright, Joanna; Baune, Bernhard T; Bertolín, Sara; Bralten, Janita; Bruin, Willem B; Bülow, Robin; Chen, Jian; et al. (Translational psychiatry, 2020)
This review summarizes the last decade of work by the ENIGMA (Enhancing NeuroImaging Genetics through Meta Analysis) Consortium, a global alliance of over 1400 scientists across 43 countries, studying the human brain in health and disease. Building on large-scale genetic studies that discovered the first robustly replicated genetic loci associated with brain metrics, ENIGMA has diversified into over 50 working groups (WGs), pooling worldwide data and expertise to answer fundamental questions in neuroscience, psychiatry, neurology, and genetics. Most ENIGMA WGs focus on specific psychiatric and neurological conditions, other WGs study normal variation due to sex and gender differences, or development and aging; still other WGs develop methodological pipelines and tools to facilitate harmonized analyses of "big data" (i.e., genetic and epigenetic data, multimodal MRI, and electroencephalography data). These international efforts have yielded the largest neuroimaging studies to date in schizophrenia, bipolar disorder, major depressive disorder, post-traumatic stress disorder, substance use disorders, obsessive-compulsive disorder, attention-deficit/hyperactivity disorder, autism spectrum disorders, epilepsy, and 22q11.2 deletion syndrome. More recent ENIGMA WGs have formed to study anxiety disorders, suicidal thoughts and behavior, sleep and insomnia, eating disorders, irritability, brain injury, antisocial personality and conduct disorder, and dissociative identity disorder. Here, we summarize the first decade of ENIGMA's activities and ongoing projects, and describe the successes and challenges encountered along the way. We highlight the advantages of collaborative large-scale coordinated data analyses for testing reproducibility and robustness of findings, offering the opportunity to identify brain systems involved in clinical syndromes across diverse samples and associated genetic, environmental, demographic, cognitive, and psychosocial factors.
Keywords: depresivní porucha unipolární; Reproducibility of Results; mozek; neurozobrazování; Depressive Disorder, Major; Humans; Magnetic Resonance Imaging; lidé; Neuroimaging; magnetická rezonanční tomografie; reprodukovatelnost výsledků; Brain